CPF: is it meeting its original objective? - Chua, Jeniffer Swee Lian (2014)
In 1955, the Central Provident Fund (CPF) was set up to provide financial security for workers during retirement or when they are no longer able to work due to physical incapacity. CPF is a major part of Singapore’s social security system based on savings and insurance. Over the years, it has taken care of not only a member’s retirement, home-ownership and health care needs but also provided financial protection to CPF members and their families through its insurance schemes. Both the employer and employee contribute to the fund. The rates of contribution have been changed over the years so as to ensure that the employee accumulates sufficient funds for his retirement in real terms, taking into account Singapore’s economic performance and expected inflation. Members are allowed to withdraw their CPF savings upon reaching age 55 and after setting aside a minimum sum in the retirement account.